THE ROLE OF PAWNSHOPS IN KUR FINANCING FOR ECONOMIC DEVELOPMENT IN KUPANG CITY - Betsyebalia, Princessa; Ballo, Fransina W.; Kiak, Novi Theresia (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to identify and describe the role of pawnshops inKUR (People’s Business Credit) financing for economicdevelopment in Kupang City using a descriptive qualitativeapproach. The research subjects were employees and staff at PT.Pegadaian (Credit Provision Unit) and KUR recipients from thepawnshop. Data were collected through observation, interviews,and documentation techniques. The data sources in this studyconsisted of primary and secondary data. The research findingsindicate that the Pension Fund of the NTT Regional DevelopmentBank experienced a funding deficit. The results also show that thePeople’s Business Credit (KUR) financing provided by pawnshopssignificantly helps MSMEs (Micro, Small, and MediumEnterprises) manage financial resources for operations, run theirbusinesses, increase income, and improve community performance.MSME income increased, and if the increase continues afterreceiving KUR financing, pawnshops may expand their financingsimulations to larger amounts, provided the loans are performingand income continues to grow after receiving KUR support fromthe pawnshop.